Mister Shivers: A Walk in the Dark and Other Scary Stories - Brallier, Max; Rubegni, Letizia (New York : Scholastic, Inc., 2022)
A collection of five scary stories, first featuring Jason, sleeping over at his uncle Henrys house, who needs to take a long, dark walk to the bathroom only to find someone is waiting for him inside.
Ages 5-7.
Grades K-1.
Keywords: Short stories; Horror fiction